2015
DOI: 10.1007/s00464-015-4537-7
|View full text |Cite
|
Sign up to set email alerts
|

Where are my instruments? Hazards in delivery of surgical instruments

Abstract: BackgroundUnavailability of instruments is recognised to cause delays and stress in the operating room, which can lead to additional risks for the patients. The aim was to provide an overview of the hazards in the entire delivery process of surgical instruments and to provide insight into how Information Technology (IT) could support this process in terms of information availability and exchange.MethodsThe process of delivery was described according to the Healthcare Failure Mode and Effects Analysis methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The tray management time involves everything outside of the OR and central sterilization department. Guedon et al [13] estimated 355 minutes dedicated to set management per case. No variance was provided, so a 20% coefficient of variation was imputed for a standard deviation of 71 minutes.…”
Section: Probability Distributions For Each Activity Variablementioning
confidence: 99%
See 2 more Smart Citations
“…The tray management time involves everything outside of the OR and central sterilization department. Guedon et al [13] estimated 355 minutes dedicated to set management per case. No variance was provided, so a 20% coefficient of variation was imputed for a standard deviation of 71 minutes.…”
Section: Probability Distributions For Each Activity Variablementioning
confidence: 99%
“…New techniques and technologies that foster greater efficiency, reduce unanticipated spending, and minimize patient complications will be critical to accommodate the continuing growth in healthcare utilization along with the associated resource requirements. For example, streamlining the surgical instrumentation is commonly emphasized for improving efficiency in the OR as well as hospital operations and would greatly support TKA in the outpatient setting by reducing the need for handling, storage, and sterilization of instruments [8,9,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 The unavailability of instruments during an intervention has been recognized to cause delays and stress in the OR, which can lead to additional patient risk. 24 Instruments are unavailable, for instance, if the tray contains a defective instrument and this is needed by the surgeon. Usually, instruments are labelled as defective during an intervention by the scrub nurse.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the fact that this entire process of sterilisation, delivery and use of surgical instruments is time consuming, it also represents an important aspect of performing safe surgery. A previous study has shown that there is a large amount of hazards throughout the entire delivery process of surgical instruments 15. The unavailability of surgical instruments represented around 40% of equipment-related incidents in the OR 16 17.…”
Section: Introductionmentioning
confidence: 99%